PENGARUH EFEKTIVITAS PLATFORM DIGITAL TERHADAP KINERJA PEGAWAI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Dadang Priatna; Arif Syabani; Dinda Ridho Permana; Muhammad Nahdiatu Solihin; Neng Wangsih; Ressa Novianti (JRPA - Journal of Regional Public Administration, 2022)
The purpose of this research is to find out how well the effectiveness of implementing digital platform, to find out how well employees are performing, to find out the relationship between the effectiveness of implementing digital platforms with increased performance, and to find out how much influence the effectiveness of implementing digital platforms has on improving performance during the pandemic in the Archives Service. and the Sumedang Regency Library. The method used in this research is descriptive analysis method with quantitative approach and the type of statistic used is inferential statistics with saturated sampling technique. The number of samples studied were 61 respondents. The analysis used includes the calculation of the percentage, the correlation coefficient test, the significance test, and the determination coefficient test. Based on the results of the research, it can be described that the effectiveness of the implementation of the digital platform at the Sumedang Regency Archives and Library Service with the dimensions of right policy, right implementation, right target, right environment, right process, and policy evaluation. Produces a percentage of 78.7% and can be categorized as good, as well as the results of Employee Performance at the Archives and Library Service of Sumedang Regency with the dimensions of quantity, quality, time effectiveness, cost efficiency, work behavior. Produces a percentage of 78.6% and can be categorized as good. The relationship between the Effectiveness of the Digital Platform Implementation on Employee Performance in the Archives and Libraries Service of Sumedang Regency is in the position of 0.787 Strong. Meanwhile, the effect of the Effectiveness of the Digital Platform Application on Employee Performance reached 61.9%, the remaining 38.1% was influenced by other factors not examined by researchers called the epsilon factor.